Center of Excellence in Type 2 Inflammation: an Organizational Model of Multidisciplinarity Management of the Patients Affected by Type 2 Inflammation Diseases - Marie, Ferrucci Silvia; Simona, Tavecchio; Luisa, Angileri; Francesco, Blasi; Paolo, Brambilla; Massimiliano, Buoli; Elisa, Colombo; Alice, D’adda; Marco, Dubini; Monica, Ferraroni; et al. (Archives of Clinical and Biomedical Research, 2021)
Atopic diseases affect millions of patients worldwide, with the greatest impact on children and young adults. Type 2 inflammation is the underlying mechanism for the development of inflammation and barrier defect in all the atopic diseases as asthma, atopic dermatitis, chronic rhinosinusitis with nasal polyps, eosinophil esophagitis. In our practice we deal every day with a lot of patients in treatment with dupilumab for AD and we realized that almost all of these patients were affected by one or more allergic diseases. Based on this real life experience we decided to create a multidisciplinary group named “Center of Excellence: type 2 disorders” composed by a pneumologist, an allergist, an oculist, an otorhinolaryngologist, a gastroenterologist, a dermatologist, a psychiatrist / psychologist. The group's scientific and research objectives are to optimize the patient’s management, to improve multidisciplinary research and to create a specialization pathway to trainee dedicated physicians qualified in type 2 disorders. We created a multidisciplinary questionnaire, the “Red Flag questionnaire”, self administered to patient in order to find the presence of type 2 disorders and to orient subsequently clinical evaluations.